2021
DOI: 10.11622/smedj.2021045
|View full text |Cite
|
Sign up to set email alerts
|

Guidance for the clinical management of infants born to mothers with suspected/confirmed COVID-19 in Singapore

Abstract: In this paper, we provide guidance to clinicians who care for infants born to mothers with suspected/confirmed COVID-19 during this current pandemic. We reviewed available literature and international guidelines based on the following themes: delivery room management; infection control and prevention strategies; neonatal severe acute respiratory syndrome coronavirus 2 testing; breastfeeding and breastmilk feeding; rooming-in of mother-infant; respiratory support precautions; visiting procedures; de-isolation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Universally testing visitors for SASR-COV-2 infection was recommended in seven publications [ 25 , 28 , 48 , 56 , 61 , 63 , 65 ]. Four papers proposed using video and teleconferences as an alternative to direct visits to labor and delivery units [ 64 , 65 , 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Universally testing visitors for SASR-COV-2 infection was recommended in seven publications [ 25 , 28 , 48 , 56 , 61 , 63 , 65 ]. Four papers proposed using video and teleconferences as an alternative to direct visits to labor and delivery units [ 64 , 65 , 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only 4 of 56 papers [ 18 , 55 , 64 , 72 ] addressed SSC specifically for mothers with confirmed infection ( Figure 4 ). In general, we observed that 70% (39 out of the 56) of analysed publications concluded that SSC should be allowed or recommended [ 17 , 18 , 27 , 32 , 36 , 42 , 44 , 47 , 49 , 51 , 54 , 55 , 57 , 59 , 60 , 65 , 66 , 69 , 70 , 71 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. In 19% (7 papers) it was directly indicated that, regarding SSC, pre-pandemic recommendations should not be changed and routine care should be provided [ 18 , 42 , 47 , 69 , 82 , 86 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pregnant women and infants are especially vulnerable to COVID-19, due to the higher risk of morbidities and mortality in infected mothers, in addition to the early uncertainties regarding vertical and perinatal transmissions to their newborns (8). Implementing training on management of the mothernewborn dyad affected by COVID-19 was complicated due to the varied recommendations, and the need for inter-disciplinary inter-specialty collaboration (9)(10)(11)(12)(13)(14). This article describes the combined approach of 3 restructured hospitals in Singapore: (a) KK Women's and Children's Hospital, (b) National University Hospital, and (c) Singapore General Hospital; in preparing and training neonatal HCWs during the COVID-19 pandemic, as well as lessons learnt during this process.…”
Section: Introductionmentioning
confidence: 99%